The Paradox of Publicity - Kovács, Balázs; Sharkey, Amanda J. (Administrative Science Quarterly, 2014)
Although increases in status often lead to more favorable inferences about quality in subsequent evaluations, in this paper, we examine a setting in which an increase to an actor’s status results in less favorable quality evaluations, contrary to what much of sociological and management theory would predict. Comparing thousands of reader reviews on Goodreads.com of 64 English-language books that either won or were short-listed for prestigious book awards between 2007 and 2011, we find that prizewinning books tend to attract more readers following the announcement of an award and that readers’ ratings of award-winning books tend to decline more precipitously following the announcement of an award relative to books that were named as finalists but did not win. We explain this surprising result, focusing on two mechanisms whereby signals of quality that tend to promote adoption can subsequently have a negative impact on evaluation. First, we propose that the audience evaluating a high-status actor or object tends to shift as a result of a public status shock, like an award, increasing in number but also in diverse tastes. We outline how this shift might translate into less favorable evaluations of quality. Second, we show that the increase in popularity that tends to follow a status shock is off-putting to some, also resulting in more negative evaluations. We show that our proposed mechanisms together explain the negative effect of status on evaluations in the context of the literary world.